ANALISIS KEBIJAKAN DIVIDEN SERTA KINERJA KEUANGAN YANG BERDAMPAK PADA NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wachidatul Hasanah; Dian Anita Sari (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
The purpose of this research is to prove the impact of dividend policy and financial performance on the value of food and beverage companies listed on the IDX. The operational variable definition in this study uses the dependent variable firm value, while the independent variables are dividend policy and financial performance. The research population is a food and beverage company listed on the IDX. Data collection technique using purposive sampling. The number of research samples is 10 companies with a total of 50 observations. Data analysis techniques with descriptive statistical analysis, classical assumption tests (multicollinearity, autocorrelation, heteroscedasticity, and normality), hypothesis testing and multiple linear regression analysis. The results of the analysis show that dividend policy (DPR) partially has a significant positive impact on firm value and financial performance (ROA) has an insignificant positive impact on firm value. The determination test shows an adjusted R2 value of 0.356, which means that the variable firm value can be explained by the two independent variables of dividend policy and financial performance of 35.6%, while the remaining 64.4% is explained by other factors outside this study.